Effect of mechanical fastener induced pre-stress on power efficiency of soft PZT energy harvesters. (25th January 2020) - Nall, George; Gamboa, Bryan; Estrada, Maximilian; Guo, Ruyan; Bhalla, Amar S.
Abstract: Experiments to determine the effects of mechanical fastener induced pre-stress on a piezoelectric energy harvester (PEH) were conducted. Using a mechanical pre-stress fixture and an electro-dynamic MTS material tester, experiments conducted on soft-PZT showed that are optimized PEH by modulating the magnitude of pre-stress induced on the soft-PZT. Experiments also showed that by adjusting the number of mechanical fasteners used to induce the pre-stress, the energy harvesting capabilities of a PEH may be further optimized.